Combined 5-Fluorouracil and Low Molecular Weight Heparin for the Prevention of Postoperative Proliferative Vitreoretinopathy in Patients With Retinal Detachment: A Meta-Analysis - Chen, Chen; Chen, Peng; Liu, Xia; Li, Hua (Frontiers in Medicine, 2021)
Background: Postoperative proliferative vitreoretinopathy (PVR) remains a dilemma for retinal surgeons. We performed literature search and meta-analyses to figure out whether combined 5-fluorouracil (5-FU) and low molecular weight heparin (LMWH) treatment was effective in improving the primary success of vitrectomy and preventing postoperative PVR occurrence in patients with retinal detachment (RD). Methods: Databases including PubMed, Embase, the Cochrane library and CNKI were searched from inception to May 2021. Comparative studies approaching the effects of combined 5-FU and LMWH on postoperative PVR were included. Quality assessment was performed using RoB 2 and ROBINS-I tool. Study data were pooled using Review manager 5.4.1. The main outcomes were: the primary success of vitrectomy at 6 months and the postoperative PVR occurrence. The additional outcomes were: number of patients underwent vitreoretinal reoperations, and the number of vitreoretinal reoperations due to postoperative PVR. Subgroup analyses and sensitivity analyses were also performed. Results: 6 clinical trials with a total of 1208 participants were included. We found that combined 5-FU and LMWH infusion didn’t improve the primary success of vitrectomy at 6 months (RR = 1.00, 95% CI = 0.95, 1.07, P = 0.89, I2 = 50%). Also, the conjunct therapy had no effect on reducing number of patients underwent vitreoretinal reoperations (RR = 1.00, 95% CI = 0.78, 1.28, P = 1.00, I2 = 42%). The overall effect of the treatment on preventing postoperative PVR was negative. However, in patients with PVR grade C (PVRC) before intervention, 5-FU and LMWH treatment significantly reduced PVR occurrence. Visual acuity was not different between treatment and control groups. Nevertheless, in one RCT, a significant reduction of VA was observed in the treatment group in macular-sparing RD patients. No complications were attributed to the conjunct therapy. Conclusions: Combined 5-FU and LMWH treatment neither improved the primary success of vitrectomy at 6 months nor decreased number of patients underwent vitreoretinal reoperations. Thus, the treatment should not be routinely used in vitrectomy for RD patients. However, the treatment proved beneficial in reducing postoperative PVR in patients with PVRC before intervention. More high-quality clinical trials are needed to confirm the results.